2022
DOI: 10.7717/peerj.13339
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of agricultural waste in the enhancement of biological denitrification of aquaculture wastewater

Abstract: Nitrogen pollution in aquaculture wastewater can pose a significant health and environmental risk if not removed before wastewater is discharged. Biological denitrification uses external carbon sources to remove nitrogen from wastewater; however, these carbon sources are often expensive and require significant energy. In this study, we investigated how six types of agricultural waste can be used as solid carbon sources in biological denitrification. Banana stalk (BS), loofah sponge (LS), sorghum stalk (SS), sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…The pore structure and pore size of RS and CC increased significantly after carbon source release ( Figures 4A , B ). Gao et al (2022) also observed the same phenomenon. This change is caused by the fact that agricultural waste contains crude fiber or lignin, which makes it difficult to degrade, and provides more pore structure with soluble substances, which may also be the reason for the large amount of carbon released from agricultural waste.…”
Section: Resultssupporting
confidence: 63%
“…The pore structure and pore size of RS and CC increased significantly after carbon source release ( Figures 4A , B ). Gao et al (2022) also observed the same phenomenon. This change is caused by the fact that agricultural waste contains crude fiber or lignin, which makes it difficult to degrade, and provides more pore structure with soluble substances, which may also be the reason for the large amount of carbon released from agricultural waste.…”
Section: Resultssupporting
confidence: 63%
“…When the HRT was increased to 28, 32, and 36 h, the ENC of WH-DR decreased, the inhibition of NO 2 − -N reductase was weakened, and NO 2 − -N was completely removed as nitrogen. Adding plant carbon sources may increase the risk of secondary pollution, such as nitrogen release and incomplete nitrogen removal ( Gao et al, 2022 ); However, in this study, the removal process of TN and NO 3 − -N showed a similar pattern ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 60%
“…Data were collected as previously described in Zhang et al (2020) and Tu et al (2010) . More details on these methods have been described in our previous study ( Gao et al, 2022 ). Specifically, NH 4 + -N concentrations were measured using the spectrophotometric method with salicylic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By-products from alcohol production in terms of their potential application as external carbon can be the best option (Czerwionka et al, 2012). External carbon source from several types of waste such as use of external carbon sources derived from biowaste (Katsou et al, 2014), food waste (X.-C. Feng et al, 2021), agricultural waste (S. Gao et al, 2022) and other types of waste can be utilized for this purpose. Thus, after reviewing several studies around the globe, it has been concluded that denitrification and addition of suitable carbon source are best combination for wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%